HEALTH EDUCATION AS A PRACTICE IN MATERNAL AND CHILD CARE: EXPERIENCE REPORT WITH PREGNANT WOMEN - Araújo de Souza, Daniely; Felipe Coêne de Souza, Jorge; de Almeida Filho, Orlando; Cristina Candido, Andreia; Ferreira dos Santos, Leonardo; da Silva Oliveira, Jessica; Gravinese Salomão, Larissa; Cristiane e Silva Figueira, Maura (Health and Society, 2023)
This is an experience report with pregnant women, accompanied by the Basic Family Health Unit of Jardim Noroeste – Campo Grande/MS, in partnership with the Education Program for Work for Health. The proposed objective relates the experience of academics from undergraduate courses in Psychology and Nursing at Centro Universitário Unigran Capital in carrying out educational practices with pregnant women. Finally, the intervention fulfilled its objective of interacting with the pregnant women in a playful and relaxed way in order to raise their awareness regarding childhood vaccination.